Evaluation After Cochlear Implant Surgery: Correlation of Clinical Outcome and Imaging Findings using Flat-detector CT - Stock, Annika; Bozzato, Victoria; Kloska, Stephan; Bozzato, Alessandro; Hoppe, Ulrich; Hornung, Joachim; Dörfler, Arnd; Struffert, Tobias (Clinical Neuroradiology, 2020)
Purpose: Assessment of the cochlear implant (CI) electrode array position using flat-detector computed tomography (FDCT) to test dependence of postoperative outcome on intracochlear electrode position. Methods: A total of 102 patients implanted with 107 CIs underwent FDCT. Electrode position was rated as 1) scala tympani, 2) scala vestibuli, 3) scalar dislocation and 4) no deconvolution. Two independent neuroradiologists rated all image data sets twice and the scalar position was verified by a third neuroradiologist. Presurgical and postsurgical speech audiometry by the Freiburg monosyllabic test was used to evaluate auditory outcome after 6 months of speech rehabilitation. Results: Electrode array position was assessed by FDCT in 107 CIs. Of the electrodes 60 were detected in the scala tympani, 21 in the scala vestibuli, 24 electrode arrays showed scalar dislocation and 2 electrodes were not placed in an intracochlear position. There was no significant difference in rehabilitation outcomes between scala tympani and scala vestibuli inserted patients. Rehabilitation was also possible in patients with dislocated electrodes. Conclusion: The use of FDCT is a reliable diagnostic method to determine the position of the electrode array. In our study cohort, the electrode position had no significant impact on postoperative outcome except for non-deconvoluted electrode arrays.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Cochlear implantation; Deafness; Dyna-CT; Misplaced cochlear implant electrode array; Rehabilitation